EFL Students’ Bilingual Community: A Sociolinguistic Study of Language Choice and Its Implications - Endang Susilawati; Eusabinus Bunau (Indonesian Journal of EFL and Linguistics, 2025)
This research was a sociolinguistic study focusing on bilingualism and language choice involving students from the English Education Study Program (EESP) as participants who were presumably members of a bilingual speech community. The objective of the research was to describe the profile of the bilingual community members with their sociolinguistic background, to analyze the patterns of language choice that occurred, and how they represent the speakers’ sociolinguistic competence in social interaction, and to interpret how the language patterns imply the role of the English in the community. A small-scale survey was conducted with non-participant observation using questionnaires and documentary sources as the tools for data collection. The research concluded that students of EESP were firmly verified as bilingual speech community members. They not only shared common stuff dealing with their academic right and duties, but also common languages as their repertoires with the same knowledge of appropriateness for the language choice practice. The choice considered the social contexts in addition to the intelligibility of the language to the participants. The co-occurrence of the choice showed that the rules of alternation existed, but were bendable. It did not represent any situation of diglossia. The occurrence of the patterns represented how the speakers’ sociolinguistic competence controlled the practice of the language choice. As an implication, English played additional roles for them to not only show their social status identity, but also as the language of education, as well as a language to build their global social networking.